A CFD-adjoint reverse design of transverse rib profile for enhancing thermo-hydraulic performance in the solar air heater. (October 2022) - Zhang, Pu; Xia, Peng; Guo, Xueyan; Xie, Shaozhang; Ma, Wensheng
Abstract: Artificial ribs interrupting the viscous sublayer beneath the absorbing plate are used to enhance SAH heat efficiency. In the present study, the CFD-adjoint reverse design method is developed to intelligently design the rib profile. Based on the zero-order CFD solution, the shape sensitivity of the rib profile is calculated by the CFD-adjoint solver, which identifies the profile characteristics to improve thermo-hydraulic performance ( THPP ). According to the shape sensitivity, the reverse design is conducted with geometrical constraints, optimization algorithms, and mesh deformation. To maximize THPP, five novel ribs are reversely designed under Reynolds numbers ranging from 4000 to 16000. The flow and heat transfer characteristics of the reversely designed ribs indicate the CFD-adjoint reverse design is in accord with the theory that turbulence enhances heat transfer in the boundary layer. The Nusselt number of the novel ribs is averagely 1.9 times compared with the smooth. The THPP of the novel ribs approaches the local maximum at the design Reynolds number with the average THPP of 1.51.